Pre-planting fertilizer application practices in rubber plantations - Dissanayake D M A P; Abeywardena V; Puhambugoda C R (Journal of the National Institute of Plantation Management, 2001)
A study on pre-planting fertilizer application practices in rubber plantations was done as part of a survey on the extent of adoption of agronomic practices in rubber plantations. Although, only very limited number of bare rooted budded stumps received planting hole application of fertilizers, tendency was more for planting hole fertilization of poly bagged plants during field establishment. Several incorrect practices commonly adopted in estates were identified and possibilities of avoiding such situations are discussed.
Keywords: Fertilizer application